Development of Composite Material for Wind Turbine Blades - Prince Yaw Andoh; Anthony Agyei-Agyemang; Peter Oppong Tawiah; Charles Kofi Kafui Sekyere; Charles McCarthy Asante (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2021)
Rapid increases in the prices of conventional turbine blade making materials as well as future sustainability issues is attracting research interest in the development of polymer composites for turbine blade applications. This study examines the suitability of using a novel bamboo fibre and recycled plastics composite developed for wind turbine blade application. Bamboo fibre was extracted from raw bamboo by chemical and mechanical processes. Recycled High Density Polyethylene (HDPE) was collected, cut into pieces, cleaned and combined with extracted bamboo fibre to form the composite. The percentage ratio of fibre content in the ten specimens ranged from 2.5% to 25%. A series of mechanical tests were conducted on the specimens, including tensile test, impact test, water absorption test and sun radiation test. Results established that as the percentage of bamboo fibre in the specimen increased, the tensile strength and impact energy also increased. Water absorption and sun radiation tests conducted on specimen X revealed no meaningful impact its mechanical properties. Hence, the most significant deduction from this study is that the specimen with 25% bamboo fibre and 75% HDPE matrix possesses the quality that qualifies it to be used as a material for wind turbine blade fabrication.